2017
DOI: 10.3991/ijet.v12i01.6485
|View full text |Cite
|
Sign up to set email alerts
|

A Constructivism-based 3D Scene Display Teaching System for Wushu Teaching

Abstract: Abstract-With the introduction of the teaching theory of constructivism and the development of virtual 3D technology, multimedia courseware production is required to enhance the authenticity of teaching situation, expand the interaction of teaching courseware, and carry out 3D network teaching. This paper designed a constructivism-based 3D scene display teaching system. By using ASP.NET and WEB3D as the core technologies and combining SQL SERVER technology, this system can run on the Internet in the form of we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…The technology of the programme implementation was based on the results of the research which was carried out by the scientists of the Department of Public Administration and Management of IFNTUOG and dealt with the formation of a structural and functional model of ATC (Panasiuk, 2018), improvements in the technology of mindset reengineering for implementation of changes (Petrenko et al, 2017) and other related topics. The choice is explained by the fact that the learning is the process in which the learners generate meaning and construct understanding on the grounds of their individual knowledge and experience (Jin, 2017). The training activities were realised in a pervasive-learning environment, which, according to Shubina and Kulakli (2019), is important both for improving cognitive processes and for increasing intrinsic motivation.…”
Section: Methodsmentioning
confidence: 99%
“…The technology of the programme implementation was based on the results of the research which was carried out by the scientists of the Department of Public Administration and Management of IFNTUOG and dealt with the formation of a structural and functional model of ATC (Panasiuk, 2018), improvements in the technology of mindset reengineering for implementation of changes (Petrenko et al, 2017) and other related topics. The choice is explained by the fact that the learning is the process in which the learners generate meaning and construct understanding on the grounds of their individual knowledge and experience (Jin, 2017). The training activities were realised in a pervasive-learning environment, which, according to Shubina and Kulakli (2019), is important both for improving cognitive processes and for increasing intrinsic motivation.…”
Section: Methodsmentioning
confidence: 99%
“…The results above thus prove that a lesson or learning that is based on constructivism theory is still relevant in the 21st century. Constructivism theory creates understanding based on the knowledge obtained from the actual environment and students' experience (Jin, 2017) so that learning becomes more meaningful (Iskander, 2014). The learning process generated in constructivism theory is not only manifested in the form of joint activities, interactions, and cooperation in building knowledge based on reality or social problems, but also through direct practice in the life of the student itself (Sukardi, 2017;Sukardi, 2016).…”
Section: Fig 5 Screenshot Of One Of the Groups Uploading Their Project To Instagrammentioning
confidence: 99%
“…Literature [10] verified the effectiveness of composite bioactive artificial cones composed of nano-hydroxyapatite and other components through the feedback of treatment practice; very effective in the treatment of thoracolumbar ligament injuries in martial arts athletes, and the treatment program followed the biomechanical principles. Literature [11] built a three-dimensional scenario martial arts teaching framework centered on constructivist theory, which helps to improve the teaching effect of martial arts. Literature [12] examined the performance of a wushu teaching model based on intelligent classroom and multimedia technology and found that the teaching model can assist in recognizing and correcting wushu movements in teaching and has rich and diversified teaching content, which greatly stimulates students' interest in learning wushu.…”
Section: Introductionmentioning
confidence: 99%